2020
DOI: 10.21203/rs.3.rs-21295/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Prenatal Depression and Anxiety Levels in Low Risk Pregnancy Among Iranian Women: A Prospective Study

Abstract: Background There is limited information on the changes in uncomplicated pregnancies. Therefore, in the present study, the changes of depression and anxiety changes in uncomplicated pregnancies during the prenatal period was evaluated.Method This longitudinal study was performed on 256 pregnant women at the beginning of the first trimester of pregnancy. Inclusion criteria included the absence of pre-pregnancy depression and anxiety and poor pregnancy history. Exclusion criteria were the incidence of pregnancy c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The average duration between data collection and publication was 2,018.187 ± 1.709 in the studies included in the analysis. The studies were conducted in Israel (Adler et al, 2019), United States (Gildner et al, 2020; Kalmbach et al, 2019; Kinser et al, 2018; Perzow et al, 2021), Turkey (Akgor et al, 2021; Alan et al, 2020; Nacar & Taşhan, 2019; Sel et al, 2019), Ethiopia (Bante et al, 2021; Belay et al, 2018; Duko et al, 2019; Gebremichael et al, 2018; Habtamu Belete et al, 2019; Shitu Ayen et al, 2020; Tesfaye & Agenagnew, 2021; Tiki et al, 2020), Bangladesh (Begum & Biswas, 2020), Italy (Cena et al, 2020; Ravaldi & Vannacci, 2020), China (Dong et al, 2021; Lau et al, 2018; Lin et al, 2021; Mo et al, 2018; Yang et al, 2021; Yu et al, 2020; Zhang et al, 2021; Zhang, Yang, et al, 2020), Denmark (Ertmann et al, 2020), South Africa (Govender et al, 2020; Kaiyo-Utete et al, 2020), Iran (Hamzehgardeshi et al, 2021; Kazemi & Dadkhah, 2022; Saadati et al, 2021), Finland (Laitinen et al, 2021), Ghana (Lillie et al, 2020), Vietnam (Luong-Thanh et al, 2021), Croatia (Mikšić et al, 2018), Malez either (Nasreen et al, 2018), India (Sheeba et al, 2019; Venkatesh et al, 2019), Pakistan (Sabir et al, 2019; Shahid et al, 2020), Poland (Smyka et al, 2020; Stepowicz et al, 2020), Thailand (Tuksanawes et al, 2020), and the Netherlands (Zilver et al, 202...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average duration between data collection and publication was 2,018.187 ± 1.709 in the studies included in the analysis. The studies were conducted in Israel (Adler et al, 2019), United States (Gildner et al, 2020; Kalmbach et al, 2019; Kinser et al, 2018; Perzow et al, 2021), Turkey (Akgor et al, 2021; Alan et al, 2020; Nacar & Taşhan, 2019; Sel et al, 2019), Ethiopia (Bante et al, 2021; Belay et al, 2018; Duko et al, 2019; Gebremichael et al, 2018; Habtamu Belete et al, 2019; Shitu Ayen et al, 2020; Tesfaye & Agenagnew, 2021; Tiki et al, 2020), Bangladesh (Begum & Biswas, 2020), Italy (Cena et al, 2020; Ravaldi & Vannacci, 2020), China (Dong et al, 2021; Lau et al, 2018; Lin et al, 2021; Mo et al, 2018; Yang et al, 2021; Yu et al, 2020; Zhang et al, 2021; Zhang, Yang, et al, 2020), Denmark (Ertmann et al, 2020), South Africa (Govender et al, 2020; Kaiyo-Utete et al, 2020), Iran (Hamzehgardeshi et al, 2021; Kazemi & Dadkhah, 2022; Saadati et al, 2021), Finland (Laitinen et al, 2021), Ghana (Lillie et al, 2020), Vietnam (Luong-Thanh et al, 2021), Croatia (Mikšić et al, 2018), Malez either (Nasreen et al, 2018), India (Sheeba et al, 2019; Venkatesh et al, 2019), Pakistan (Sabir et al, 2019; Shahid et al, 2020), Poland (Smyka et al, 2020; Stepowicz et al, 2020), Thailand (Tuksanawes et al, 2020), and the Netherlands (Zilver et al, 202...…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review included findings about 13 studies on the depression symptoms measurement scores during pregnancy (Akgor et al, 2021; Dong et al, 2021; Gebremichael et al, 2018; Gildner et al, 2020; Kazemi & Dadkhah, 2022; Kinser et al, 2018; Lau et al, 2018; Lillie et al, 2020; Lin et al, 2021; Luong-Thanh et al, 2021; Perzow et al, 2021; Sheeba et al, 2019; Zilver et al, 2021). Depression symptoms mean score obtained from these studies was found 6.109 ± 0.577 (95% CI: 4.978–7.239; z : 10.591, I 2 : 99.604; p < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations